Decoloration rates of a photomerocyanine dye as a visual probe into hydrogen bonding interactions1. Issue 23 (21st March 2015) - Ciampi, Simone; Eggers, Paul K.; Haworth, Naomi L.; Darwish, Nadim; Wagner, Pawel; Coote, Michelle L.; Wallace, Gordon G.; Raston, Colin L.
<x xml:space="preserve">Abstract</x> A visual marker for probing hydrogen-bonding effects in static and thin film fluidic systems.